KEDUDUKAN HUKUM PEMERINTAH DAERAH DALAM KERJASAMA DAERAH DENGAN PIHAK KETIGA - Yakim, Muhammad (Katalogis, 2017)
Cooperation between an autonomous city/regency government and third parties in this reformation era is unavoidable, due to many problems unsolvable by the government. The concept of city/regency cooperation is crucial since it is represented in an agreement under private law or contract law. On the other hands, the city/regency cooperation is in factÂ has to be executed by a public official in the line with existing legality principles pursuant to the administrative law. In other words, in city/regency cooperation the contract law is not fully enforceable. The action taken by the city/regency government is under diffusion theory. The city/regency cooperation which is strongly affected by discretion entails many problems due to lack of observance as to when the state administration is involved in public law and when the private law is potential to lead to authority abuses.Â The principle of no authority without accountability also affects to free authority or discretion by city/regency government. It was a normative research adopting law and conceptual approaches. The legal materials were analyzed by first collecting primary legal materials, secondary legal materials and non-legal materials. Next, the normative concepts in those materials were studied, analyzed, described, estimated and explained. Based on the results of the research, it was concluded that It was prohibited for a city/regency government to cooperate with central government and associate with other business entities.Â The city/regency government simply needed to adopt the concept of official assistance or central government facilitation. The cooperation between a city/regency government and a third party and any other parties as provided in Article 363 Section (2) letter b of Law Number 23 Year 2014 about City/Regency Government providing that a city/regency government remains accountable and litigable both officially and individually in compliance with the principle of no authority without accountability.